Super water-resistant sulfur-poisoning low-temperature scr denitration catalyst, preparation method and application thereof

CN122999281APending Publication Date: 2026-10-30WUXI LONGYUAN ENVIRONMENTAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611145303.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

本发明方法提供了一种具有疏水亲气纳米花结构的超耐水硫中毒低温SCR脱硝催化剂。该催化剂以CeZrO2氧化物为活性主体,通过Sn元素掺杂改性并负载于CuxZn1-x-ZIF载体,构筑出兼具高活性与强抗中毒能力的新型催化体系。与传统低温脱硝催化剂相比,本发明催化剂在含有15% H2O、150ppm SO2的工况条件下仍保持优异的低温脱硝效率,抗水、耐硫及低温活性得到协同提升,特别适用于垃圾焚烧等复杂烟气工况下的低温脱硝净化,具有广阔的工业化应用前景。此外,本发明催化剂活性组分配方及其制备工艺简单,对环境污染小。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999281A_ABST
    Figure CN122999281A_ABST
Patent Text Reader

Abstract

The application provides a super-water-resistant sulfur-poisoning low-temperature SCR denitration catalyst and a preparation method and application thereof. The SCR denitration catalyst provided by the application has high denitration activity and excellent water resistance and sulfur resistance under low-temperature working conditions. The preparation method comprises the following steps: S1, tin salt, cerium salt, zirconium salt and oxalic acid are mixed, and are ground in the presence of a surfactant; the mixture is dried and then calcined to obtain a Sn-CeZrO2 catalyst; S2, copper salt and zinc salt are dissolved in anhydrous methanol to obtain a ZIF metal precursor solution; the Sn-CeZrO2 catalyst is added to the solution, and is uniformly dispersed by ultrasonic treatment to obtain a solution A; S3, an anhydrous methanol solution of 2-methyl imidazole is used as a solution B; the solution B is added to the solution A, and is stirred and reacted at room temperature; the reaction product is washed by centrifugation with anhydrous methanol, and is dried to obtain the SCR denitration catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of SCR denitrification catalyst technology, specifically to a low-temperature SCR denitrification catalyst with ultra-high resistance to water and sulfur poisoning, its preparation method, and its application. Background Technology

[0002] Waste incineration technology is widely used due to its advantages of rapid volume reduction and resource recovery, but the NOx and other pollutants it releases seriously threaten the ecological environment and public health. Ammonia selective catalytic reduction (NH3-SCR) technology has become a key development direction due to its excellent low-temperature activity, high denitrification efficiency, and low ammonia slip. However, the temperature of waste incineration flue gas (<250℃) does not match the activity temperature window (300–400℃) of commercial V2O5-WO3(MoO3) / TiO2 denitrification catalysts, and the high water content (15%–20%) in the flue gas makes it easy for SO2, alkali metals, HCl, and other components to poison and deactivate the catalyst. Although existing research has improved catalyst performance through component optimization or structural design, developing catalysts suitable for waste incineration flue gas conditions faces challenges such as insufficient low-temperature activity, unclear anti-poisoning mechanisms, and poor anti-poisoning stability.

[0003] Metal-organic frameworks (MOFs) formed by the self-assembly of metal cations and organic ligands have attracted much attention in the field of denitrification catalysis due to their tunable pore size, numerous tunable active sites, and high specific surface area. ZIF-8 has a simple synthesis method, a specific surface area far exceeding that of general metal oxide catalysts, an ordered pore structure, and excellent hydrothermal stability, making it a potential candidate for metal oxide supports.

[0004] How to solve the problems that existing SCR denitrification catalysts have poor tolerance to water and sulfur dioxide under low-temperature operating conditions, are prone to deactivation, and thus have low low-temperature denitrification efficiency, making it difficult to meet the requirements, remains one of the technical challenges that urgently need to be overcome in this field. Summary of the Invention

[0005] To address at least one deficiency in existing technologies, this invention provides a low-temperature SCR denitrification catalyst with superior resistance to water and sulfur poisoning, its preparation method, and its applications. The SCR denitrification catalyst provided by this invention not only exhibits high denitrification activity under low-temperature operating conditions but also demonstrates excellent water and sulfur resistance.

[0006] To achieve its objective, the present invention provides the following technical solution: This invention provides a method for preparing a low-temperature SCR denitrification catalyst that is highly resistant to water and sulfur poisoning, comprising the following steps: S1. Tin salt, cerium salt, zirconium salt and oxalic acid are mixed and ground in the presence of surfactant. The resulting mixture is dried and then calcined to obtain Sn-CeZrO2 catalyst. S2. Dissolve copper salt and zinc salt in anhydrous methanol to obtain ZIF metal precursor solution, add Sn-CeZrO2 catalyst obtained in step S1 to it, and ultrasonically disperse it evenly to obtain solution A. S3. Using an anhydrous methanol solution of 2-methylimidazole as solution B, add solution B to solution A, stir and react at room temperature, then wash the reaction product with anhydrous methanol by centrifugation, and dry to obtain the SCR denitration catalyst.

[0007] Preferably, in step S1, the molar ratio of Sn in the tin salt, Ce in the cerium salt, and Zr in the zirconium salt is 0.1-0.3:6-8:2-4; The molar ratio of oxalic acid to the total amount of metal ions in the tin salt, cerium salt and zirconium salt used in step S1 is 1.5-2:1.

[0008] Preferably, in step S1, the surfactant is selected from one or more of PEG 600, CTAB, and SDS; The ratio of the amount of surfactant to the total mass of the tin salt, cerium salt, and zirconium salt is 2%-12%.

[0009] Preferably, in step S1, the tin salt, cerium salt, zirconium salt and oxalic acid are first mixed and ground for 5-10 minutes, and then the surfactant is added and the mixture is further mixed and ground for 30-60 minutes.

[0010] Preferably, in step S2, the proportion of Cu element is 50-80% relative to the total amount of Cu and Zn elements in the copper salt and the zinc salt; And / or, in step S2, the amount of Sn-CeZrO2 catalyst added is 0.1-0.2 g relative to every 100 mL of solution A.

[0011] Preferably, in step S2, the total concentration of metal elements in the ZIF metal precursor solution is 0.1-1.0 mol / L.

[0012] Preferably, the molar ratio of the total amount of copper salt and zinc salt in step S2 to the amount of 2-methylimidazole used in step S3 is 1:5-7.

[0013] Preferably, in step S1, the drying is carried out at 60-80°C; And / or, in step S1, the calcination temperature is 400-700℃ and the calcination time is 3-6 h; And / or, in step S3, the drying is vacuum drying, and the drying temperature is 60-80℃; And / or, in step S3, the reaction is stirred at room temperature for 6-12 hours; And / or, in step S3, the concentration of 2-methylimidazole in solution B is 1-1.5 mol / L; And / or, in step S1, the tin salt is one or more of SnCl4·5H2O and SnCl2·2H2O; the cerium salt is one or more of Ce(NO3)3·6H2O and cerium carbonate; and the zirconium salt is one or more of Zr(NO3)4·5H2O and zirconium carbonate. And / or, in step S2, the copper salt is Cu(NO3)2·3H2O; the zinc salt is Zn(NO3)2·6H2O.

[0014] Another aspect of the present invention provides a super-water- and sulfur-poisoned low-temperature SCR denitrification catalyst prepared by the preparation method described above; The SCR denitrification catalyst has a nanoflower structure.

[0015] In another aspect, the present invention provides the application of the SCR denitrification catalyst described above, wherein the SCR denitrification catalyst is used in flue gas denitrification and purification.

[0016] The technical solution provided by this invention has the following beneficial effects: This invention provides a super-water- and sulfur-poison-resistant low-temperature SCR denitrification catalyst with a hydrophobic and anaerobic nanoflower structure. The catalyst uses CeZrO2 oxide as the active host, modified by Sn doping and supported on Cu. x Zn 1-x A novel catalytic system with high activity and strong resistance to poisoning was constructed using a ZIF support. Compared with traditional low-temperature denitrification catalysts, the catalyst of this invention maintains excellent low-temperature denitrification efficiency even under conditions containing 15% H2O and 150ppm SO2. Its resistance to water and sulfur, as well as its low-temperature activity, are synergistically improved, making it particularly suitable for low-temperature denitrification and purification under complex flue gas conditions such as waste incineration, and it has broad prospects for industrial application. Furthermore, the formulation of the active components and the preparation process of the catalyst of this invention are simple, resulting in minimal environmental pollution. Attached Figure Description

[0017] Figure 1 This refers to the Sn-CeZrO2 / Cu prepared in Example 2 of this invention. 0.7 Zn 0.3 -Scanning electron microscopy image of ZIF composite catalyst Detailed Implementation To facilitate understanding of the present invention, the following description, in conjunction with embodiments, will further illustrate the invention. It should be understood that the following embodiments are merely for a better understanding of the invention and do not imply that the invention is limited to these embodiments.

[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The term "and / or" may be used herein to include any and all combinations of one or more of the associated listed items.

[0019] This invention provides a method for preparing a low-temperature SCR denitrification catalyst that is highly resistant to water and sulfur poisoning, comprising the following steps: S1. Tin salt, cerium salt, zirconium salt and oxalic acid are mixed and ground in the presence of surfactant. The resulting mixture is dried and then calcined to obtain Sn-CeZrO2 catalyst. S2. Dissolve copper salt and zinc salt in anhydrous methanol to obtain ZIF metal precursor solution, add Sn-CeZrO2 catalyst obtained in step S1 to it, and ultrasonically disperse it evenly to obtain solution A. S3. Using an anhydrous methanol solution of 2-methylimidazole as solution B, add solution B to solution A and stir the reaction at room temperature. Then, wash the reaction product with anhydrous methanol by centrifugation until clean, for example, washing multiple times (specifically, more than three times) until clean. The supernatant should be free of obvious suspended matter upon visual inspection. After drying, the SCR denitration catalyst, namely Sn-CeZrO2 / Cu, is obtained. x Zn 1-x -ZIF.

[0020] The method of this invention first prepares a Sn-CeZrO2 catalyst by mixing tin salt, cerium salt, zirconium salt, and oxalic acid in the presence of a surfactant via grinding and calcination. Then, the catalyst is added to a ZIF metal precursor solution prepared with copper and zinc salts in anhydrous methanol, and dispersed to obtain solution A. Next, an anhydrous methanol solution of 2-methylimidazole is added to solution A and reacted at room temperature. Finally, after post-treatment, the SCR denitrification catalyst of this invention is obtained. The catalyst provided by the preparation method of this invention is an ultra-water-resistant, sulfur-poisoned, low-temperature SCR denitrification catalyst with a hydrophobic and anaerobic nanoflower structure. This catalyst uses CeZrO2 oxide as the active host, modified by Sn element doping and supported on Cu. x Zn 1-x -ZIF support was used to construct a novel catalytic system that combines high activity with strong resistance to poisoning. Sn doping increased the surface acidity of the catalyst and effectively induced the formation of a large amount of Ce³⁺. + With the presence of surface oxygen vacancies, Cu significantly inhibits the adsorption and poisoning of SO2 on the catalyst surface. x Zn 1-x- The ZIF nanoflower structure endows the catalyst with excellent hydrophobic and gas-philic properties. Compared with traditional low-temperature denitrification catalysts, the catalyst of this invention maintains excellent low-temperature denitrification efficiency even under operating conditions containing 15% H2O and 150ppm SO2. Water resistance, sulfur resistance and low-temperature activity are synergistically improved, making it particularly suitable for low-temperature denitrification and purification under complex flue gas conditions such as waste incineration, and it has broad prospects for industrial application.

[0021] The catalyst provided by this invention effectively solves the problem that existing SCR denitrification catalysts have poor tolerance to water and sulfur dioxide under low-temperature operating conditions, are prone to deactivation, and thus have low low-temperature denitrification efficiency, making it difficult to meet the application requirements. The catalyst prepared by the method of this invention can significantly improve the low-temperature denitrification efficiency of the catalyst, maintain excellent denitrification performance under water and sulfur-containing conditions, and the formulation of the catalyst active components and its preparation process are simple, with minimal environmental pollution.

[0022] Preferably, in step S1, the molar ratio of Sn in the tin salt, Ce in the cerium salt, and Zr in the zirconium salt is 0.1-0.3:6-8:2-4; The molar ratio of oxalic acid to the total amount of metal ions in the tin, cerium, and zirconium salts used in step S1 is 1.5-2:1, for example, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, etc. Controlling the amount of oxalic acid within this preferred range, compared to higher or lower amounts, not only allows for a more complete reaction between the oxalic acid and the metal salts, but also results in a catalyst with high crystallinity, smaller crystal size, and better dispersibility, ultimately leading to a higher-performance low-temperature SCR denitration catalyst.

[0023] Preferably, in step S1, the surfactant is selected from one or more of PEG 600, CTAB, and SDS; The ratio of the amount of surfactant to the total mass of the tin salt, cerium salt, and zirconium salt is 2%-12%, for example, 2%, 4%, 6%, 8%, 10%, 12%, etc. Introducing surfactants of preferred types and amounts during the grinding process results in a catalyst with a larger specific surface area, providing more active sites, promoting the adsorption of reactant gases on the catalyst, increasing the number of surface oxygen vacancies, and giving the prepared catalyst superior sulfur resistance.

[0024] Preferably, in step S1, the tin salt, cerium salt, zirconium salt, and oxalic acid are first mixed and ground for 5-10 minutes, and then the surfactant is added and the mixture is further ground for 30-60 minutes. In this invention, the grinding and calcination method used in step S1 is simple to operate, the preparation conditions are easy to control, the yield is high, the cost is low, and there is little pollution. Moreover, compared with preparation methods such as precipitation and sol-gel methods, it avoids hard agglomeration that easily occurs in the liquid phase. The prepared Sn-CeZrO2 catalyst has highly dispersed SnO2 species and strong interactions between SnO2 and cerium oxide / zirconia, resulting in a catalyst with excellent catalytic activity.

[0025] Preferably, in step S2, the proportion of Cu element relative to the total amount of Cu and Zn elements in the copper salt and zinc salt is 50-80%, for example, 50%, 60%, 70%, 80%, etc. The inventors have discovered that as the Cu doping concentration gradually reaches approximately 50%, the catalyst morphology begins to change, gradually transforming from the original dodecahedral crystal structure into a unique nanoflower structure, exhibiting unique characteristics such as branching and cavity formation. These structural elements are more conducive to promoting the transport of reactants and gaseous products within the system, with exposed surfaces containing more active sites and a larger interfacial contact area, promoting the continuous reaction of ammonia and nitrogen oxides. When the doping concentration exceeds approximately 80%, the nanoflower structure breaks and collapses, hindering the transport of reactants and gaseous products within the system, reducing exposed active sites, and thus decreasing catalyst activity.

[0026] Preferably, in step S2, the amount of Sn-CeZrO2 catalyst added is 0.1-0.2g relative to every 100mL of solution A, for example, 0.1g, 0.15g, 0.2g, etc.

[0027] Preferably, in step S2, the total concentration of metal elements in the ZIF metal precursor solution is 0.1-1.0 mol / L, such as 0.1 mol / L, 0.4 mol / L, 0.6 mol / L, 1.0 mol / L, etc.

[0028] Preferably, the molar ratio of the total amount of copper salt and zinc salt in step S2 to the amount of 2-methylimidazole used in step S3 is 1:5-7.

[0029] In some examples, in step S1, the drying is carried out at 60-80°C; Preferably, in step S1, the calcination temperature is 400-700℃ (e.g., 400℃, 500℃, 600℃, 700℃, etc.), and the calcination time is 3-6 h; In some examples, in step S3, the drying is vacuum drying at a temperature of 60-80°C; In some examples, in step S3, the stirring reaction is carried out at room temperature for 6-12 hours; In some examples, in step S3, the concentration of 2-methylimidazole in solution B is 1-1.5 mol / L; In some examples, in step S1, the tin salt is one or more of SnCl4·5H2O and SnCl2·2H2O; the cerium salt is one or more of Ce(NO3)3·6H2O and cerium carbonate; and the zirconium salt is one or more of Zr(NO3)4·5H2O and zirconium carbonate. In some examples, in step S2, the copper salt is Cu(NO3)2·3H2O; and the zinc salt is Zn(NO3)2·6H2O.

[0030] Compared with the prior art, the present invention has at least the following significant advantages: The ultra-water- and sulfur-poison-resistant low-temperature SCR denitrification catalyst prepared in this invention uses 2-methylimidazolium as the metal framework, Cu / Zn as the metal source, and synthesizes Cu... x Zn 1-x -ZIF MOF support, which has a large specific surface area and a hydrophobic and anaerobic nanoflower structure; the catalyst obtained based on this support in this invention alleviates the condensation of H2O in the catalyst pores, improves the catalyst's adsorption and activation capacity for NH3, and inhibits the competitive adsorption of H2O and reactants NH3 / NO on the catalyst surface; in the catalyst of this invention, Zr 4+ Sn 4+ The synergistic effect between these metals appropriately weakens the redox performance of the Sn-CeZrO2 catalyst, enhances its acid strength, and provides more oxygen vacancies and Ce... 3+ It inhibits the adsorption of SO2 on active sites by adsorbing oxygen species, thus significantly improving the catalyst's resistance to sulfur poisoning and enhancing its catalytic performance.

[0031] Another aspect of the present invention provides a super-water- and sulfur-poisoned low-temperature SCR denitrification catalyst prepared by the preparation method described above; The SCR denitrification catalyst has a nanoflower structure.

[0032] In another aspect, the present invention provides the application of the SCR denitrification catalyst described above, wherein the SCR denitrification catalyst is used in flue gas denitrification and purification.

[0033] The present invention will be further illustrated by the following embodiments, but it should not be construed as the present invention being limited to these embodiments.

[0034] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in this technical field can be followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0035] Example 1: (1) Weigh 0.1 mmol SnCl4·5H2O, 7 mmol Ce(NO3)3·6H2O, 3 mmol Zr(NO3)4·5H2O and 17.2 mmol oxalic acid and grind them thoroughly in an agate mortar for 10 min. Then add 0.3 g PEG 600 and continue to mix and grind for 45 min. Place the mixture obtained by grinding in an oven at 65℃ and dry for 24 h. Then transfer it to a muffle furnace and calcine at 600℃ for 4 h to obtain Sn-CeZrO2 catalyst.

[0036] (2) Dissolve 6 mmol Cu(NO3)2·3H2O and 4 mmol Zn(NO3)2·6H2O in 80 ml of anhydrous methanol solution to obtain ZIF metal precursor solution; then add 0.08 g Sn-CeZrO2 catalyst prepared in step (1) to the solution, and disperse it evenly by ultrasonication, and record it as solution A; (3) Dissolve 0.06 mol of 2-methylimidazole in 50 mL of anhydrous methanol, and denote this as solution B. Slowly add solution B to solution A and stir thoroughly at room temperature for 10 h. After the reaction is complete, centrifuge and wash with anhydrous methanol until clean. Discard the supernatant after washing, and dry the washed solid in a vacuum drying oven at 60 °C for 12 h to obtain Sn-CeZrO2 / Cu 0.6 Zn 0.4 -ZIF.

[0037] Example 2: (1) Weigh 0.2 mmol SnCl4·5H2O, 6 mmol Ce(NO3)3·6H2O, 4 mmol Zr(NO3)4·5H2O and 17.2 mmol oxalic acid and grind them thoroughly in an agate mortar for 10 min. Then add 0.35 g CTAB and continue to mix and grind for 45 min. Place the mixture obtained from grinding in an oven at 65 ℃ for 24 h and then transfer it to a muffle furnace and calcine it at 600 ℃ for 4 h to obtain the Sn-CeZrO2 catalyst.

[0038] (2) Dissolve 7 mmol Cu(NO3)2·3H2O and 3 mmol Zn(NO3)2·6H2O in 80 ml of anhydrous methanol solution, then add 0.08 g of Sn-CeZrO2 catalyst prepared in step (1), and disperse it evenly by ultrasonication. This solution is called solution A. (3) Dissolve 0.06 mol of 2-methylimidazole in 50 mL of anhydrous methanol, and denote this as solution B. Slowly add solution B to solution A and stir thoroughly at room temperature for 10 h. After the reaction is complete, centrifuge and wash with anhydrous methanol until clean. Discard the supernatant after washing, and dry the washed solid in a vacuum drying oven at 60 ℃ for 12 h to obtain Sn-CeZrO2 / Cu 0.7 Zn 0.3 -ZIF.

[0039] Example 3 (1) Weigh 0.3 mmol SnCl4·5H2O, 8 mmol Ce(NO3)3·6H2O, 2 mmol Zr(NO3)4·5H2O and 17.2 mmol oxalic acid and grind them thoroughly in an agate mortar for 10 min. Then add 0.4 g PEG 600 and continue to mix and grind for 45 min. Place the mixture obtained by grinding in an oven at 65℃ and dry for 24 h. Then transfer it to a muffle furnace and calcine at 600℃ for 4 h to obtain Sn-CeZrO2 catalyst.

[0040] (2) Take 8 mmol Cu(NO3)2·3H2O and 2 mmol Zn(NO3)2·6H2O and dissolve them in 80 ml of anhydrous methanol solution, then add 0.08 g of Sn-CeZrO2 catalyst prepared in step (1), and disperse it evenly by ultrasonication. This solution is called solution A. (3) Dissolve 0.06 mol of 2-methylimidazole in 50 mL of anhydrous methanol, and denote this as solution B. Slowly add solution B to solution A and stir thoroughly at room temperature for 10 h. After the reaction is complete, centrifuge and wash with anhydrous methanol until clean. Discard the supernatant after washing, and dry the washed solid in a vacuum drying oven at 60 ℃ for 12 h to obtain Sn-CeZrO2 / Cu 0.8 Zn 0.2 -ZIF.

[0041] Example 4 The procedure is the same as in Example 1, except that: In step (1), the amount of SnCl4·5H2O used is 0.1 mmol; the amount of oxalic acid used is 15.2 mmol; the 0.3 g PEG600 is replaced with 0.3 g SDS; the calcination is carried out at 500℃ for 6 h.

[0042] In step (2), the amount of Sn-CeZrO2 catalyst added is 0.15g.

[0043] In step (3), the time for thorough stirring at room temperature is 6 hours.

[0044] Comparative Example 1 (no load on the carrier) (1) Weigh 0.1 mmol SnCl4·5H2O, 7 mmol Ce(NO3)3·6H2O, 3 mmol Zr(NO3)4·5H2O and 17.2 mmol oxalic acid and grind them thoroughly in an agate mortar for 10 min. Then add 0.3 g PEG 600 and continue to mix and grind for 45 min. Place the mixture obtained by grinding in an oven at 65℃ and dry for 24 h. Then transfer it to a muffle furnace and calcine at 600℃ for 4 h to obtain the Sn-CeZrO2 catalyst.

[0045] Comparative Example 2 (without introducing Sn) (1) Weigh 6 mmol Ce(NO3)3·6H2O, 4 mmol Zr(NO3)4·5H2O and 17.2 mmol oxalic acid into an agate mortar and grind them thoroughly for 10 min. Then add 0.35 g CTAB and continue to mix and grind for 45 min. Place the mixture obtained from grinding in an oven at 65℃ and dry for 24 h. Then transfer it to a muffle furnace and calcine it at 600℃ for 4 h to obtain CeZrO2 catalyst.

[0046] (2) Dissolve 7 mmol Cu(NO3)2·3H2O and 3 mmol Zn(NO3)2·6H2O in 80 ml of anhydrous methanol solution, then add 0.08 g of Sn-CeZrO2 catalyst prepared in step (1), and ultrasonically disperse it evenly. This solution is called solution A. (3) Dissolve 0.06 mol of 2-methylimidazole in 50 mL of anhydrous methanol, and denote this as solution B. Slowly add solution B to solution A and stir thoroughly at room temperature for 10 h. After the reaction is complete, centrifuge and wash with anhydrous methanol until clean. Discard the supernatant after washing, and dry the washed precipitate in a vacuum drying oven at 60 ℃ for 12 h to obtain CeZrO2 / Cu. 0.7 Zn 0.3 -ZIF.

[0047] Comparative Example 3 (support without Cu) (1) Weigh 0.1 mmol SnCl4·5H2O, 7 mmol Ce(NO3)3·6H2O, 3 mmol Zr(NO3)4·5H2O and 17.2 mmol oxalic acid and grind them thoroughly in an agate mortar for 10 min. Then add 0.3 g PEG 600 and continue to mix and grind for 45 min. Place the mixture obtained by grinding in an oven at 65℃ and dry for 24 h. Then transfer it to a muffle furnace and calcine at 600℃ for 4 h to obtain the Sn-CeZrO2 catalyst.

[0048] (2) Dissolve 10 mmol Zn(NO3)2·6H2O in 80 ml of anhydrous methanol solution, then add 0.08 g of Sn-CeZrO2 catalyst prepared in step (1), and disperse it evenly by ultrasonication. This solution is denoted as solution A. (3) Dissolve 0.06 mol of 2-methylimidazole in 50 mL of anhydrous methanol and label it as solution B. Slowly add solution B to solution A and stir thoroughly at room temperature for 10 h. After the reaction is complete, centrifuge and wash with anhydrous methanol until clean. Discard the supernatant after washing and dry the washed solid in a vacuum drying oven at 60 °C for 12 h to obtain Sn-CeZrO2 / Zn-ZIF.

[0049] Comparative Example 4 The process was carried out in accordance with Example 1, except that PEG600 was not added during the grinding process in step (1).

[0050] Comparative Example 5 The procedure was carried out in accordance with Example 1, except that in step (1), oxalic acid was replaced with citric acid.

[0051] Comparative Example 6 The process was carried out in accordance with Example 1, except that in step (1), the Sn-CeZrO2 catalyst was prepared by precipitation method. The specific operation was as follows: 0.1 mmol SnCl4·5H2O, 7 mmol Ce(NO3)3·6H2O and 3 mmol Zr(NO3)4·5H2O were dissolved in 100 ml of deionized water to prepare a metal precursor solution. 0.1 mol / L KHCO3 aqueous solution was slowly added dropwise to the above solution and the pH was adjusted to 9-11. After the addition was completed, the solution was aged at room temperature for 1.5 h. The resulting solution was washed three times by centrifugation with deionized water. The precipitate was dried at 80 °C for 12 h. The dried product was placed in a muffle furnace and calcined at 600 °C for 4 h to obtain the Sn-CeZrO2 catalyst.

[0052] Comparative Example 7 The procedure was carried out in accordance with Example 1, except that in step (2), the amount of Cu(NO3)2·3H2O was 9 mmol and the amount of Zn(NO3)2·6H2O was 1 mmol.

[0053] The denitrification catalyst finally obtained in the embodiments of the present invention has a nanoflower structure. Figure 1 Sn-CeZrO2 / Cu prepared in Example 2 0.7 Zn 0.3 The scanning electron microscope image of the ZIF composite catalyst is shown. The detection results of other examples are similar to those of Example 2, all showing the morphology of the nanostructured catalyst, which will not be described in detail here.

[0054] Performance testing and denitrification experiments were conducted on the denitrification catalysts of the embodiments and comparative examples of this invention. Detailed test results are shown in Table 1. The test methods are as follows: The test used simulated flue gas, with gas components including NOx, NH3, O2, and carrier gas N2. The space velocity was set at 30,000 h⁻¹. -1 NOx concentration was 500 ppm, NH3 / NO x The molar ratio was 1, and the O2 concentration was 2 vol%. When SO2 and water vapor were introduced, the SO2 concentration in the simulated flue gas was 150 ppm, and the H2O content was 15 vol%. The reaction temperature was controlled in the range of 160-200℃. During the reaction, starting from the initial temperature, a test temperature point was set at regular intervals (e.g., 160℃, 180℃, and 200℃). At each test temperature point, the temperature was kept constant for 1 hour. After the reaction reached a steady state, the gas composition at the reactor inlet and outlet was tested using a Fourier transform infrared gas analyzer (GASMET, Finland, model DX4000).

[0055] Table 1. Results of denitrification catalytic activity determination of the catalysts prepared in the examples and comparative examples before and after the introduction of SO2 and H2O.

[0056] In Table 1, "before introduction" refers to the measurement results before SO2 and H2O are introduced during the test, and "after introduction" refers to the measurement results after SO2 and H2O are introduced during the test.

[0057] As shown in Table 1, the catalysts in Examples 1-4 of this invention achieve a denitrification efficiency of over 90% in the low-temperature range of 160-200℃ under conditions without the introduction of 15% H2O and 150ppm SO2. After introducing water vapor and sulfur dioxide, the catalyst denitrification efficiency fluctuates less, and the efficiency decreases only slightly at 200℃, sometimes by as little as 1%. In contrast, the comparative examples initially exhibited poor denitrification activity, and the decrease in denitrification efficiency was more significant after introducing 15% H2O and 150ppm SO2. This indicates that Sn-doped CeZrO2 oxide and Cu... x Zn 1-x The ZIF nanoflower support exhibits a significant synergistic effect, endowing the catalyst with excellent water and sulfur resistance. The low-temperature SCR denitrification catalyst prepared by the method of this invention not only has high denitrification activity but also excellent water and sulfur resistance.

[0058] This invention appropriately weakens the redox performance of CeZrO2 catalyst by Sn doping modification, increases the number of Brønsted acid sites and the content of chemisorbed oxygen species, and significantly enhances the catalyst's resistance to sulfur poisoning; simultaneously, it combines with Cu, which has a high specific surface area and hydrophobic-hydrophilic properties. xZn 1-x The ZIF nanoflower support exhibits a synergistic effect, further enhancing the catalyst's resistance to water and sulfur. The catalyst prepared using the method of this invention can withstand 15% H2O water vapor and 150 ppm SO2 sulfur poisoning environments, and its denitrification efficiency can still be stably maintained above 85% in a low-temperature range of 160℃~200℃.

[0059] It is readily understood that the above embodiments are merely illustrative examples for clear explanation and do not imply that the invention is limited thereto. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a low-temperature SCR denitrification catalyst with super resistance to water and sulfur poisoning, characterized in that, Includes the following steps: S1. Tin salt, cerium salt, zirconium salt and oxalic acid are mixed and ground in the presence of surfactant. The resulting mixture is dried and then calcined to obtain Sn-CeZrO2 catalyst. S2. Dissolve copper salt and zinc salt in anhydrous methanol to obtain ZIF metal precursor solution, add Sn-CeZrO2 catalyst obtained in step S1 to it, and ultrasonically disperse it evenly to obtain solution A. S3. Using an anhydrous methanol solution of 2-methylimidazole as solution B, add solution B to solution A, stir and react at room temperature, then wash the reaction product with anhydrous methanol by centrifugation, and dry to obtain the SCR denitration catalyst.

2. The preparation method according to claim 1, characterized in that, In step S1, the molar ratio of Sn in the tin salt, Ce in the cerium salt, and Zr in the zirconium salt is 0.1-0.3:6-8:2-4; The molar ratio of oxalic acid to the total amount of metal ions in the tin salt, cerium salt and zirconium salt used in step S1 is 1.5-2:

1.

3. The preparation method according to claim 1, characterized in that, In step S1, the surfactant is selected from one or more of PEG600, CTAB, and SDS; The ratio of the amount of surfactant to the total mass of the tin salt, cerium salt, and zirconium salt is 2%-12%.

4. The preparation method according to any one of claims 1-3, characterized in that, In step S1, the tin salt, cerium salt, zirconium salt and oxalic acid are first mixed and ground for 5-10 minutes, and then the surfactant is added and the mixture is continued to be ground for 30-60 minutes.

5. The preparation method according to any one of claims 1-3, characterized in that, In step S2, the proportion of Cu element is 50-80% relative to the total amount of Cu and Zn elements in the copper salt and the zinc salt. And / or, in step S2, the amount of Sn-CeZrO2 catalyst added is 0.1-0.2 g relative to every 100 mL of solution A.

6. The preparation method according to any one of claims 1-3, characterized in that, In step S2, the total concentration of metal elements in the ZIF metal precursor solution is 0.1-1.0 mol / L.

7. The preparation method according to any one of claims 1-3, characterized in that, The molar ratio of the total amount of copper salt and zinc salt in step S2 to the amount of 2-methylimidazole used in step S3 is 1:5-7.

8. The preparation method according to any one of claims 1-3, characterized in that, In step S1, the drying is carried out at 60-80°C; And / or, in step S1, the calcination temperature is 400-700℃ and the calcination time is 3-6 h; And / or, in step S3, the drying is vacuum drying, and the drying temperature is 60-80℃; And / or, in step S3, the reaction is stirred at room temperature for 6-12 hours; And / or, in step S3, the concentration of 2-methylimidazole in solution B is 1-1.5 mol / L; And / or, in step S1, the tin salt is one or more of SnCl4·5H2O and SnCl2·2H2O; the cerium salt is one or more of Ce(NO3)3·6H2O and cerium carbonate; and the zirconium salt is one or more of Zr(NO3)4·5H2O and zirconium carbonate. And / or, in step S2, the copper salt is Cu(NO3)2·3H2O; the zinc salt is Zn(NO3)2·6H2O.

9. A super-water- and sulfur-poisoned low-temperature SCR denitrification catalyst prepared by the preparation method according to any one of claims 1-8; The SCR denitrification catalyst has a nanoflower structure.

10. The application of the SCR denitrification catalyst according to claim 9, characterized in that, The SCR denitrification catalyst is used in flue gas denitrification and purification.